Sidewalk Quality and its Impact on Pedestrian Activities on Dr. Mansyur Street, Medan Selayang - Ruben Simangunsong; Cut Nuraini; Abdiyanto Abdiyanto (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Sidewalks are a crucial element of urban infrastructure that support pedestrian mobility. However, on Jalan Dr. Mansyur, Medan Selayang, sidewalk conditions present various problems, such as damaged surfaces, a lack of accessibility facilities, and the presence of street vendors occupying the lanes. This study aims to analyze the impact of sidewalk quality on pedestrian activity by examining three main factors: the physical condition of the sidewalk, environmental safety, and accessibility. Using a mixed methods approach, the sample for the quantitative approach was taken using a stratified random sampling method with a total of 150 respondents. Quantitative data were analyzed using descriptive statistics and SPSS software, while qualitative data were collected through in-depth interviews with key informants. The results showed that sidewalk accessibility had the strongest relationship with pedestrian activity (correlation coefficient 0.72), followed by the physical condition of the sidewalk (0.68) and environmental safety (0.55). Minimal accessibility factors, such as the lack of special lanes for the disabled, proved to be the main obstacle to pedestrian activity. In addition, the damaged physical condition of the sidewalk and the use of sidewalks for activities that are not in accordance with their function further reduce user comfort. Based on these findings, key recommendations include physical improvements to sidewalks with regard to the principles of universal accessibility, including the addition of dedicated lanes for the disabled, repair of damaged surfaces, and reconfiguration of spaces to discourage use by street vendors. The government needs to ensure adequate street lighting to improve user safety. The public is expected to maintain the function of sidewalks by utilizing them according to their intended purpose, while future researchers are advised to explore the impact of sidewalk improvements on broader social and economic aspects, as well as consider the integration of technology in sidewalk design and management. The conclusion of this study is the need for collaborative action between the government, the community, and other relevant parties to create inclusive sidewalk infrastructure that supports active mobility.